The role of waqf in response to the challenges of peace and youth empowerment in Yobe State, Nigeria - Ibrahim Dahiru Idriss; Adibah Abdul Rahim; Ismail Mamat (Penerbit Universiti Kebangsaan Malaysia, 2024)
The study explores various causes of insecurity and unemployment among the youth in Yobe state and identifies the potential of waqf-based youth employment programs to provide peace in the state. Security challenges in the state are persistent but to ensure peace and empower the teeming youth in various capacities, various measures are put in place for the sustainable development in the state. The act of waqf endowment is a good deed commanded by Islam. Waqf has been established to provide social economic and community-based services in Muslim society. Waqf has diversified roles and benefits in the community. Waqf has been practice since the lifetime of Prophet Muhammad (PBUH) until today. The study applied a qualitative method of research which employs interview in which relevant information has been gathered from 15 selected participants in order to examine the role of waqf in addressing the designed objective and recommends the ways which waqf funds are used to efficiently empower the youth. The findings of the study show that waqf has the potential to address the menace of unemployment, insecurity, and other social vices among the youth in Yobe. The paper concludes that youth empowerment in the fields of education, health, entrepreneur, vocational skills bring positive and sustainable peace in Yobe state. The paper contributed to finding the potential of waqf institutions as perpetual charity in providing the basic societal needs that empowers the youth to attain the peaceful and prosperous Yobe society.